Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1088/0967-3334/37/10/1686
|View full text |Cite
|
Sign up to set email alerts
|

Muscle activation and energy expenditure of sedentary behavior alternatives in young and old adults

Abstract: The physiological mechanisms that underlie the metabolic benefits of breaking up sedentary behavior (SB) have yet to be determined. The purpose of this study is to compare energy expenditure (EE) and muscle activation (MA) responses to sitting and four SB alternatives in younger and older adults. Twenty-two adults, grouped by age (21-35 and 62-76 years), completed five randomly ordered 20 min tasks: (1) continuous sitting (Sit), (2) sitting on a stability ball (Ball), (3) continuous standing (Stand), (4) sitti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
(64 reference statements)
0
14
0
Order By: Relevance
“…Given that both experimental groups similarly increased, this suggests that such an enhancement occurs irrespective of the pattern of prescribed LIPA. Together with the effect that LIPA has on stimulating skeletal muscle in older adults [ 73 ], secondary enhancements to dietary pro-anabolic potential may aid with perturbing the loss of skeletal muscle mass/function during aging (sarcopenia) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that both experimental groups similarly increased, this suggests that such an enhancement occurs irrespective of the pattern of prescribed LIPA. Together with the effect that LIPA has on stimulating skeletal muscle in older adults [ 73 ], secondary enhancements to dietary pro-anabolic potential may aid with perturbing the loss of skeletal muscle mass/function during aging (sarcopenia) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…leg, thigh and back muscles; normalized against walking at 5 km/h on a treadmill) during 2 h of standing than during 2 sitting hours. In contrast, Lerma et al 13 found no significant differences in normalized upper (m. upper trapezius and m. erector spinae) and lower (m. medial gastrocnemius and m. rectus femoris) muscle activity between 20 min of standing and 20 min of sitting on a chair.…”
Section: Discussionmentioning
confidence: 86%
“…In line with this, we found no differences in activity of the rectus femoris, vastus lateralis and erector spinae muscles during active sitting compared to sitting on an office chair. Additionally, Lerma et al 13 found no differences in normalized (against maximal muscle contractions) upper (m. upper trapezius and m. erector spinae) and lower (m. medial gastrocnemius and m. rectus femoris) muscle activity during active sitting. Similarly, except for the left thoracic erector spinae, Gregory et al 27 found no significant differences in normalized (against maximal muscle contractions) muscle activity of the right thoracic erector spinae, left and right lumbar erector spinae, left and right rectus abdominis and left and right external oblique between sitting on a stability ball and sitting on an office chair in young adults (aged 25.4 ± 5.4 and 22.3 ± 1.0 years old men and women, respectively).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Standing interruptions are increasingly used as a potential intervention to reduce prolonged sedentary behaviour in youth [ 7 ]. However, experimental studies in adults are inconclusive regarding whether muscle activity and body movement during standing are sufficient to counteract potential adverse cardiometabolic effects of prolonged sitting [ 8 , 9 ]. The extent to which body movement during standing is higher than during sedentary behaviour in young people is currently unknown.…”
Section: Introductionmentioning
confidence: 99%